The Extent of Honeycombing on Computed Tomography Cannot Predict the Treatment Outcome of Patients with Acute Exacerbations of Interstitial Lung Disease. (16th November 2021) - Nishikawa, Yurika; Hara, Yu; Tagami, Yoichi; Nagasawa, Ryo; Murohashi, Kota; Aoki, Ayako; Tanaka, Katsushi; Watanabe, Keisuke; Horita, Nobuyuki; Kobayashi, Nobuaki; Yamamoto, Masaki; Kudo, Makoto; et al.
Abstract : Background . The purpose of this retrospective study was to clarify whether the presence of honeycombing on computed tomography (CT) can affect the prognosis of patients with acute exacerbations (AEs) of interstitial lung diseases (ILDs). Methods . Clinical parameters including age, sex, Charlson Comorbidity Index Score (CCIS), blood biomarkers, and 3-month mortality were retrospectively compared between the CT honeycombing present and absent groups at the diagnosis of AEs of ILDs. Results . Ninety-five patients who were on corticosteroid pulse therapy were assessed. Though log-rank tests showed that Kaplan–Meier survival curves of the high and low ground-glass opacity (GGO) score groups differed significantly in 3-month mortality in patients with AEs of idiopathic ILDs (P  = 0.007) and overall patients (P  = 0.045), there was no significant difference between the CT honeycombing present and absent groups in patients with AEs of idiopathic ILDs (P  = 0.472) and AEs of secondary ILDs (P  = 0.905), as well as of overall patients (P  = 0.600). In addition, whereas CCIS (OR, 1.436; 95% CI, 1.156–1.842; P  < 0.001) was a significant predictor of 3-month mortality in the CT honeycombing absent group, serum LDH (OR, 1.005; 95% CI, 1.002–1.007; P  = 0.001) was a significant predictor in the CT honeycombing present group. Conclusions . The clinical features of patients with or without honeycombing may differ due to the difference in prognostic factors, but these groups were found to have similar prognoses 3 months after AE onset, and clinicopathological examinations according to these groups are essential.